Adeno-associated virus-mediated gene transfer of arginine decarboxylase to the central nervous system prevents opioid analgesic tolerance - Churchill, Caroline C.; Peterson, Cristina D.; Kitto, Kelley F.; Pflepsen, Kelsey R.; Belur, Lalitha R.; McIvor, R. Scott; Vulchanova, Lucy; Wilcox, George L.; Fairbanks, Carolyn A. (Frontiers in Pain Research, 2024)
Agmatine, a decarboxylated form of L-arginine, prevents opioid analgesic tolerance, dependence, and self-administration when given by both central and systemic routes of administration. Endogenous agmatine has been previously detected in the central nervous system. The presence of a biochemical pathway for agmatine synthesis offers the opportunity for site-specific overexpression of the presumptive synthetic enzyme for local therapeutic effects. In the present study, we evaluated the development of opioid analgesic tolerance in ICR-CD1 mice pre-treated with either vehicle control or intrathecally delivered adeno-associated viral vectors (AAV) carrying the gene for human arginine decarboxylase (hADC). Vehicle-treated or AAV-hADC-treated mice were each further divided into two groups which received repeated delivery over three days of either saline or systemically-delivered morphine intended to induce opioid analgesic tolerance. Morphine analgesic dose-response curves were constructed in all subjects on day four using the warm water tail flick assay as the dependent measure. We observed that pre-treatment with AAV-hADC prevented the development of analgesic tolerance to morphine. Peripheral and central nervous system tissues were collected and analyzed for presence of hADC mRNA. In a similar experiment, AAV-hADC pre-treatment prevented the development of analgesic tolerance to a high dose of the opioid neuropeptide endomorphin-2. Intrathecal delivery of anti-agmatine IgG (but not normal IgG) reversed the inhibition of endomorphin-2 analgesic tolerance in AAV-hADC-treated mice. To summarize, we report here the effects of AAV-mediated gene transfer of human ADC (hADC) in models of opioid-induced analgesic tolerance. This study suggests that gene therapy may contribute to reducing opioid analgesic tolerance.